The prokineticin Bv8 sensitizes cutaneous terminals of female mice to heat. (23rd February 2016) - Hoffmann, T.; Negri, L.; Maftei, D.; Lattanzi, R.; Reeh, P.W.
Abstract: Background: Injection of the noxious peptide Bv8 has previously been shown to induce a biphasic thermal hyperalgesia in rodents, the first peak presumably due to peripheral sensitization. This hypothesis has never been directly confirmed. We have assessed whether Bv8 can indeed sensitize peripheral nerve fibres in the mouse to heat. Methods: We used recordings from single cutaneous fibres, cutaneous calcitonin gene‐related peptide (CGRP) release and immunostaining in nerves and plantar skin to evaluate the Bv8 effects on cutaneous nerves. Results: Application of Bv8 at nanomolar concentrations (30–310 nmol/L) to skin preparations significantly increased the heat‐induced discharge, the heat‐induced afterdischarge and reduced threshold temperature of single unmyelinated polymodal fibres. Furthermore, application of Bv8 to hind‐paw skin flaps or trigeminal ganglia significantly elevated their heat‐induced CGRP release. Capsaicin‐induced and to a lesser extent also KCl‐induced CGRP releases were also augmented after Bv8 treatment. Immunohistochemistry revealed co‐localization of prokineticin 2 (Bv8 ortholog in rodents) and CGRP in both plantar skin and nerve tissues. These results confirm that Bv8 sensitizes cutaneous nerve endings to heat, partly, although not exclusively through TRPV1 activation. Conclusion: Our results thus support the hypothesis that the first hyperalgesic phase to follow Bv8 injection to hind paws of intact animals is due to peripheral sensitization of nociceptors. What does this study add?: Our data provide mechanistic insights into the effect Bv8 application exerts on afferent nerve endings and into the concomitant development of thermal hyperalgesia.